1932
DOI: 10.1136/bmj.2.3742.583
|View full text |Cite
|
Sign up to set email alerts
|

Senescence

Abstract: OTITIS MEDIA IN SUCKLINGS MEDICAL JOURNAL 583 ILLUSTRATIVE CASES An Austrian observer had a case of an infant of 6 months, severely ill with high temperature, but showing no physical signs. The tympanic membranes were so nearly normal that he hesitated to open them, but did so; a very little pus * Read in opening a discussiort in the Section of Comparative Medicine at the Centenary Meeting of the British Medical Association, London, 1932.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

1939
1939
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 0 publications
1
38
1
Order By: Relevance
“…This is contrary to Bidder's (1932) hypothesis -in the absence of evidence that all cells are equally renewable, it does not negative theories based on cell loss renal degenerative changes, for example, do not appear histologically to be being made good, whether somatic growth is continuing or not. Neither does it follow that what holds good for the growth of the guppy in relation to aging is equally true of long-lived fish such as the sturgeon.…”
Section: Discussioncontrasting
confidence: 47%
“…This is contrary to Bidder's (1932) hypothesis -in the absence of evidence that all cells are equally renewable, it does not negative theories based on cell loss renal degenerative changes, for example, do not appear histologically to be being made good, whether somatic growth is continuing or not. Neither does it follow that what holds good for the growth of the guppy in relation to aging is equally true of long-lived fish such as the sturgeon.…”
Section: Discussioncontrasting
confidence: 47%
“…Simple clock-type processes arc becom ing suspect as explanatory analogies in ageing -it has been shown that they do not apply to the thermal coefficient of mortality in crease in Drosophila, where the age change presumably affects fixed postmitotic cells (Clarke and Maynard Smith, 1961); they may equally misrepresent the process of mortality increase in animals which are not of fixed cell number. Ageing which appears in spite of continuing growth, but can be slowed by underfeeding, is incompatible with Bidder's (1932) old hypothesis that indeterminate size implies indeterminate life-span, but compatible with recent work suggesting that somatic cells may be clonally unstable (Hayjlick and Moorhead, 1961;Krohn, 1962). Thus the hypothetical background of the senescence of fish has changed considerably in the ten years since we set out to see whether Bidder's theories could be substantiated.…”
Section: Resultsmentioning
confidence: 45%
“…Also there is an increasing awareness of the decline of selection pressures with increasing age. This principle, a central part of the theory developed here, is first recognizable in the work of Bidder (1932), and has since been stated or implied by Haldane (1941), Medawar (1953), andComfort (1956). The principle is implicit in the currently recognized definition of a lethal gene as one that results in death before the reproductive period.…”
mentioning
confidence: 77%